(untitled) (Research, Society and Development, 2022)
The prevalence of esophageal varices has increased in Brazil over the years, and some epidemiological aspects are related to this fact, having an affect on its surgical treatment. Objective: The study aimed to determine which epidemiological aspects and their impact on the hospital treatment of esophageal varices, in addition to their relationship with the number of hospitalizations and deaths. Justification: Due to the fact that this pathology is largely treated as an emergency, preventing and reducing bleeding from esophageal varices with the surgical procedures involved are important for the patient’s survival. Thus, the present study brings a need for greater understanding of the subject, since there is a lack of more recent information and more up-to-date academic studies related to the subject. Results: the number of cases during the period 2016-2020 increased, with an evident increase in the number of hospitalizations, during this same period, according to the study carried out, the most prevalent character of care in these cases was the emergency one, representing a good part of the cases, the results were also painful for the mortality rate, which has been falling over the years. Conclusion: in view of the above, the epidemiological profile found to be prevalent is male, brown, aged over 60 years and less than 7 years of schooling. In addition, it is possible to conclude that although there are several treatments for esophageal varices, surgical procedures play a prominent role in patients who adopt therapeutic failure in more conservative treatment.